(untitled) (Journal of Asian Development Studies, 2026)
Grounded in positive psychology and socio-educational theories of second language acquisition, this study investigates the direct and indirect relationships between classroom interaction and learners’ willingness to communicate (WTC) in English as a Foreign Language (EFL) settings. Specifically, it examines the mediating roles of emotional support and foreign language enjoyment (FLE), as well as their sequential chain mediation. Using a quantitative research design and structural equation modelling, data were collected from university-level EFL learners. The findings indicate that classroom interaction significantly predicts WTC both directly and indirectly. Emotional support and FLE independently mediate this relationship, and a significant chain-mediation effect further demonstrates that interaction enhances perceived emotional support, which, in turn, increases enjoyment and strengthens WTC. These results highlight the central role of affective classroom environments in fostering communicative engagement and offer pedagogical implications for creating emotionally supportive, interaction-rich EFL classrooms